The relationship between individual characteristics and HIV-related stigma in adults living with HIV: medical monitoring project, Florida, 2015-2016 - Renessa Williams; Robert Cook; Babette Brumback; Christa Cook; Miriam Ezenwa; Emma Spencer; Robert Lucero (BMC, 2020)
Abstract Background Human Immunodeficiency Virus (HIV) disproportionately affects the Southern United States, accounting for approximately 46% of people living with HIV. HIV-related stigma is recognized as a barrier to testing, treatment, and prevention efforts. However, little is known about HIV-related stigma experiences in Florida. Using data collected from the Florida Medical Monitoring Project, we sought to examine individual characteristics associated with HIV-related stigma. Methods We analyzed secondary data from the 2015-2016 Medical Monitoring Project in Florida (n = 603). Stigma was measured using the 10-item HIV Stigma Scale. Exploratory factor analysis of the HIV Stigma Scale revealed three subscales: negative self-image, anticipated, and personalized stigma. Bivariate and multivariate regression models were used to determine the individual characteristics associated with the HIV Stigma Scale. Results Multivariate analysis indicated that people with severe depression scores (OR: 3.13; CI: 1.38-7.13) and persons with disability (OR: 1.64; CI: 1.03-2.61) had significantly increased odds of higher overall stigma. In the subscale analyses, negative self-image was significantly associated with alcohol misuse (OR: 2.02; CI: 1.15-3.56) depression (OR: 2.81; CI: 1.38-5.72) and/or those who identify as homosexual (OR: 0.54; CI: 0.31-0.93). Anticipated stigma was significantly associated with people who had mild-moderate depression (OR: 3.03; CI: 1.20-7.65), severe depression (OR: 2.87; CI: 1.38-5.98), identified as Black (OR: 0.60; CI: 0.37-0.98), non-injection drug use (OR: 0.55; CI: 0.33-0.91), and/or people aged 50 years and older (OR: 0.28; CI: 0.09-0.82). Personalized stigma was not associated with any of the variables examined. Conclusions The implications of these findings reveal that certain individuals are more vulnerable to stigma. Researchers could consider distinct stigma interventions strategies based on the characteristics of specific individuals (i.e., targeting depression, disability, sexual orientation, avoidant coping, racial/ethnic groups, and youth) in Florida.